صورة المرأة في الحياة الأسرية : دراسة أدبية مقارنة في الحكايات الشعبية العربية والملايوية - Nur Aini binti Ariffin (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This comparative study focuses on the image of women in family life as a mother, wife and sister in both Arabic and Malay folk tales. It is based on 20 selected stories from two famous books: ×ikāyāt Sha'biyyah by AÍmad Ziyād MaÍbak and Himpunan 366 Cerita Rakyat Malaysia by Othman Puteh and Aripin Said. This study adopted three research methodologies: inductive, descriptive and comparative. The inductive method focused on investigating the literature on the portrayal of women in Arabic and Malay folk tales as reported in previous studies, books, journal articles, published articles and websites. The descriptive method was used to define and introduce both Arabic and Malay folk tales and describe their roles in the community. The comparative method was used to make a comparative analysis between the image of women in Arabic and Malay folk tales. The study reveals that the image of women in both folk tales shares a number of common features suggesting the universality of folk tales. Nevertheless, there are also minor differences between the two folk tales due to other factors such as environment and cultural differences as well as the storyteller's inclinations and preferences.